Excitation of durable VHF oscillations in ferrite-filled coaxial lines - Magda, I.; Mukhin, V.; Sinitsin, V.; Karelin, S.; Lebedenko, O.; Volovenko, M.; Rak, O. (Problems of Atomic Science and Technology, 2023)
Effective methods are suggested for exciting gigahertz-range oscillations in coaxial lines that contain ferrite rings and isotropic material. Within the gyrotropic section, the primary pulsed waveform gets transformed from the TEM into a TM mode. Its further development is analyzed, following the results of real-life and numerical experiments. Special attention is paid to amplitude variations of the ТМ mode, owing to the nonlinear response of the ferrite. Пропонуються ефективні методи збудження осциляцій гігагерцевого діапазону в коаксіальних лініях, що містять уставки з феритових кілець та ізотропного матеріалу. У гіротропній частині лінії первинна імпульсна хвильова форма трансформується з моди ТЕМ у моду ТМ. Проаналізовано їх подальший розвиток за результатами відповідних натурних і числових експериментів. Особливої уваги приділено варіаціям амплітуди ТМ-моди, що пов’язані з нелінійністю електромагнітного відгуку фериту.